Pengaruh NaCl Terhadap Kalus Tebu Varietas Bululawang (The Effect of NaCl on Callus of Sugarcane Varieties Bululawang) - Khoirul Bariyyah (Jurnal Agroekoteknologi, 2015)
The research was aim to study the effect of NaCl on callus of sugarcane varieties Bululawang. This experiment has been conducted in Tissue Culture Laboratory of the Faculty of Agiculture, University of Jember from December 2012 to Mei 2013. The experiment which consists of four levels concentration of NaCl : 0 g/l (K0), 4 g/l (K1), 8 g/l (K2), 12 g/l (K3), and 16 g/l (K4). Each treatment consists of four replications. The experiment consisted of three stages: callus induced, salinity strees of callus, and shoot regeneration of sugarcane on various rate NaCl. Observations conducted qualitative description of the parameters of the color of callus , callus structure and shoot regeneration. The results of this experiment indicated that the callus of sugarcane varieties Bululawang experienced salinity stres of NaCl at 4 g/l showed symptom degradation of color to yellow with sticky crumb structure. Increasing consentrations of NaCl 8-16 g/l lead callus color being tawny until black with sticky crumb structure. Salinity stres with consentrations of NaCl at 4 g/l caused callus is not able to regenerate to form buds and increase callus cell death.